Atlantis - Lewis, Ann Margaret (New York : Rosen Pub. Group, 2002)
Presents an overview of the mysteries surrounding the fabled civilization and island of Atlantis, including Plato$1 (Bs story, strange theories, and archaeological fact.s
Includes bibliographical references (p. 46) and index.
Keywords: Atlantis; Atlantis